The Pacific Island Volcanology and Its Relation to the Groundwater Features Through Magmatic Signatures - Ronald Maharaj; Azekah Swamy; Shailesh Kumar Singh; Sandeep Panchal (Sustainable Earth Trends)
The Pacific Plate is one of the heaviest tectonic plates, hosting multiple Pacific Island countries. Geological research has long provided evidence of volcanic magmatic events, which have frequently caused subsurface activities. The formation of an active ring of fires across the Pacific Ocean is a geological signature of the intense volcanic events occurring over time.  The study aims to verify the close correlation between groundwater features and volcanic magmatic events, which is evident in near-surface ground signatures and geothermal systems. Hot water springs and geysers emerge as manifestations of the active molten volcanic processes, releasing intense heat flux, gases, and pressure. Pacific Island countries exhibit common geological features, particularly in terms of parent rock materials, resulting in a unique combination of aquifer characteristics essential for long-term hydrological sustainability. The sustainability of groundwater resources is intricately linked with volcanic events and their associated signatures, which emerge abruptly over time.  Furthermore, the study is to access the correlation of the pacific geological features within Fiji and various regions and its usages in terms of implementing water resources upon the identification of the active aquifers in the terrestrial and coastal plains. Fieldwork using various tomography methods from various regional countries executed by the Secretariat of the Pacific Community through the implementation of various programs has provided various supporting evidence that the magmatic activities featured by dikes, basins, and aquifers have water holding capacity which is hydrogeological connected to the main water aquifer.